Assessment and validation of the TREAT-B score to assess the treatment eligibility of patients with chronic hepatitis B virus infection - Thanapirom, Kessarin; Suksawatamnuay, Sirinporn; Thaimai, Panarat; Treeprasertsuk, Sombat; Komolmit, Piyawat; Tangkijvanich, Pisit (Frontiers in Medicine, 2022)
Background and aims Access to Hepatitis B virus (HBV) DNA testing to determine treatment eligibility is limited in low-income countries. Therefore, this study aimed to assess and validate the TREAT-B score proposed as the treatment threshold in an Asian cohort in determining the HBV treatment eligibility. Methods A retrospective analysis was conducted on consecutive patients with treatment-naïve chronic HBV mono-infection who visited the liver clinic at Chulalongkorn University Hospital, Bangkok, Thailand, from 2016 to 2020. The 2018 American Association for the Study of Liver Diseases guideline was the reference standard. Results Overall, 825 patients with chronic HBV infection were enrolled, comprising 409 (50.4%) males, with a median age of 50 (38–58) years. Of these, 216 (26.2%), 565 (68.5%), and 377 (45.7%) were eligible for treatment based on the AASLD, TREAT-B score, and simplified WHO criteria, respectively. The area under the receiver operating characteristics curve (AUROC) of the TREAT-B ≥ 2 was better than the simplified WHO criteria (0.69 vs. 0.62, p = 0.006) for selecting patients eligible for antiviral therapy. The sensitivity and specificity of the TREAT-B ≥ 2 were 96.3% and 41.4%, respectively. Applying the TREAT-B ≥ 3 improved the specificity (89.0%) and AUROC (0.80, 95% CI 0.76–0.84, but reduced the sensitivity (70.8%) for selecting eligible patients for HBV therapy. Conclusions In resource-constrained countries where HBV DNA is unavailable, the TREAT-B score is an alternative criteria for indicating treatment eligibility. The TREAT-B score of ≥3 is highly accurate and may minimize the number of patients unnecessarily treated in Asian HBV patients.